Pengaruh Penggunaan Buku Cerita Digital terhadap Kemampuan Berbicara Anak Kelompok B di TK Negeri Pembina Mataram Tahun Ajaran 2025 - Rini Andriani; Fahruddin; Ika Rachmayani; Filsa Era Sativa (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The use of digital storybooks and the speaking ability of Group B children at TK Negeri Pembina Mataram are still underdeveloped. Therefore, engaging activities are needed to stimulate children’s speaking skills. This study aimed to examine the effect of using digital storybooks on the speaking ability of Group B children. The research employed a quantitative approach with an experimental method using a one-group pretest–posttest design involving 20 children as subjects. Data were collected through observation and documentation techniques. The data were analyzed using descriptive statistical analysis and the paired sample t-test. The normality test of the difference between pretest and posttest scores showed a significance value of 0.512 (p > 0.05), indicating that the data were normally distributed and met the assumption of normality. The linearity test resulted in a significance value of 0.891 (p > 0.05), indicating a linear relationship in the data. Hypothesis testing using the paired sample t-test yielded a t-value of 42.67 with a significance value of 0.00. Since the significance value was lower than the 5% significance level, the null hypothesis (H₀) was rejected. Thus, it can be concluded that the use of digital storybooks has a significant effect on the speaking ability of Group B children at TK Negeri Pembina Mataram.